Potential of Banana Plant Waste as Animal Feed - yanuartono - yanuartono; Alfarisa - Nururrozi; Indarjulianto - Soedarmanto; Dhasia - Ramandani; Hary - Purnamaningsih (Fakultas Peternakan, Universitas Padjadjaran, 2020)
AbstractThe availability of forage feed is one of the factors that greatly influences the success of ruminant livestock businesses. However, forage will be difficult to obtain during the dry season so that feed is generally replaced from various agricultural wastes such as rice straw, stover or corn straw and other crop wastes. At present the use of banana plant waste as animal feed varies greatly from each banana producing country. Banana by-products such as leaves, young plants, rejected fruit and stems can be used as a source of ruminant animal feed. Although the volume of banana plant waste is abundant, its utilization is limited by several factors such as the high fiber in the stems and leaves. In addition, high water content can easily damage banana plant waste so that it is often wasted. To overcome the above constraints, further processing methods are needed to increase the nutritional value. The easiest and most low-cost method of further processing is using fermentation technology. Added value of the fermentation process is being able to preserve seasonally abundant feed for subsequent feeds during periods of feed shortages. This paper aims to briefly summarize the potential and benefits of fermented banana plant waste as ruminant animal feed.Keywords: agricultural by-products, bananas, animal feed, fermentation